Comparison of Consumption of Seaweed and Soybeans on Increasing Hemoglobin Levels in Pregnant Women at the Samkai Community Health Center, Merauke Regency - Nurmiani, Ritha; Retnaningyas, Erma; Muslichah , Miftakul; Hastuti, Tri (Journal of Midwifery and Nursing, 2024)
Reduced Hb concentration during pregnancy results in reduced oxygen supply to all body tissues, causing signs and symptoms of anemia. You can increase Hb by consuming seaweed and soybean juice, because both contain iron, minerals, vitamin B complex and protein. This research aims to determine the comparison of consumption of seaweed and soybeans on increasing hemoglobin levels in pregnant women in the Samkai health center working area. Quasi-experimental research design with a one group pretest-posttest design. Using purposive sampling technique, a sample of 30 respondents was obtained, the independent variable was consumption of seaweed and soybeans. The dependent variable is an increase in Hb levels. Data collection uses observation with the Chi-Square statistical test. The research results showed that half of the respondents aged over 30 years were 17 respondents (57%), more than half of the multigravida parity respondents were 21 respondents (70%), the average Hb before being given soybeans was 9.5 gr/dl and after being given beans soybeans increased to 10.5 gr/dl while the average Hb before being given seaweed was 9.6 gr/dl and after being given seaweed the Hb increased to 10.3 gr/dl. There was an increase in Hb before and after consuming soybeans. Giving soybeans is more efficient in increasing Hb levels in pregnant women by 0.2 gr/dl compared to giving seaweed.